(untitled) (Journal of Computational Mathematics, 1992)
An extended system for codimension two bifurcation with a pure imaginary pair and a simple zero eigenvalue is proposed. Its regularity is proved. An efficient algorithm for solving the extended system is constructed. Finally, some results on the axial dispersion problem in a tubular non-adiabatic reactor is given.